Educational Activities of Research Institutions in the Field of Expert Ensuring of Justice: Urgent Issues of Administrative and Legal Regulation - O. V. Agapova (Bulletin of Kharkiv National University of Internal Affairs)
The purpose of the article is to study actual issues of administrative and legal regulation of providing educational activities to research institutions in the sphere of expert ensuring justice. It is devoted to the clarification of certain issues of the activity of research institutes of forensic examinations, which provide educational activities at the third (educational-scientific) level of higher education (preparation of applicants for higher education of the degree of doctor of philosophy). The modern administrative legislation is analysed and the proposals are given for improving educational activities, which affects the development of expert ensuring of justice in general.